Two new species of the Neotropical leafhopper genus Scoposcartula (Insecta: Hemiptera: Cicadellidae: Cicadellini) - Leal, Afonso H.; Mejdalani, Gabriel; Cavichioli, Rodney R. (Zootaxa, 2005)
The new leafhopper species Scoposcartula talitae and S. furcifera are described and illustrated. Scoposcartula talitae is based on specimens from southeastern Brazil (Espírito Santo State) and can be distinguished from other species of the genus by the crown and pronotum dark brown to black, the latter with a pair of white maculae, and by the forewings dark red with three elongate transverse white maculae. Scoposcartula furcifera is based on specimens from northeastern Brazil (Bahia State) and can be recognized by the presence of a dark brown to black inverted Y-shaped macula on the pronotum-scutellum and by its asymmetrical paraphysis, broadened medially and with the apex acute. With the addition of these two new taxa, the Neotropical leafhopper genus Scoposcartula Young contains 14 species, all occurring in Brazil.